Pumice Raft Detection Using Machine-Learning on Multispectral Satellite Imagery - Zheng, Maggie; Mittal, Tushar; Fauria, Kristen E.; Subramaniam, Ajit; Jutzeler, Martin (Frontiers in Earth Science, 2022)
Most of Earth's volcanic eruptions occur underwater, and these submarine eruptions can significantly impact large-scale earth systems (e.g., enhancing local primary production by phytoplankton). However, detecting submarine eruptions is challenging due to their remote locations, short eruption durations, lack of sea surface signature (if eruptions don't breach the surface), and the transient nature of the surface manifestations of an eruption (e.g., floating pumice clasts, hydrothermal fluids). We can utilize global satellite imagery of 10-30 m resolution (e.g., Landsat 8, Sentinel-2) to detect new eruptions; however, the large data volumes make it challenging to systematically analyze satellite imagery on global. In this study, we address these challenges by developing a new semi-automated analysis framework to detect submarine eruptions through supervised classification of satellite images on Google Earth Engine. We train our algorithm using images from the August 2019 Tongan rafts and present a case study using our methodology on satellite imagery from the Rabaul caldera region in Papua New Guinea. We potentially find a large number of new unreported pumice rafts (in ~16% of images from 2017-present). After analysis of the spatial pattern of raft sightings and ancillary geophysical and visual observations, we interpret that these rafts are not the result of a new eruption. Instead, we posit that the observed rafts represent remobilization of pumice clasts from previous historical eruptions. This novel process of raft remobilization may be common at near-shore/partially submarine caldera systems (e.g., Rabaul, Krakatau) and may have significant implications for new submarine eruption detection and volcanic stratigraphy.